Human Resource Management Practices and Performance of State-Owned Banks in Kenya - Gatheru, Caroline Njoki; Karanja, Kibiru (Human Resource and Leadership Journal, 2025)
Purpose: The purpose of this study was to determine the influence of human resources management practices on the performance of State-owned banks in Kenya. The was guided by the following specific objectives; To establish the influence of training and development, performance management, reward management and succession planning on performance of state owned banks in Kenya. The study was anchored on Abraham Maslow’s theory, Herzberg’s Two-factor theory, Equity theory and Instrumentality theory. Methodology: The study applied a descriptive research design to collect quantitative. The target population includes 350 employees from middle management and lower level management. The study employed stratified sampling sample size of 184. This study employed questionnaires as an instrument for collecting data. The study used descriptive statistics to analyze the data using percentiles, the mean and standard deviation for qualitative and inferential statistics which include correlation and regression analysis. Findings: The findings showed that training and development, performance management, reward management and succession planning had a positive influence on performance of state-owned banks in Kenya. However, reward management had insignificant influence on performance of state-owned banks in Kenya. Therefore, the concluded that training and development, performance management and succession planning as aspects of HRM practice in improving performance of state-owned banks in Kenya, while reward management was adequate to improve performance of state-owned banks in Kenya. Unique Contribution to Theory, Policy and Practice: The findings thus recommends enhancing training and development programs to better align with employees' career progression and evolving industry requirements. Banks should also strengthen appraisal systems by ensuring transparency, goal alignment, and continuous feedback mechanisms, to review and restructure their incentive systems to ensure they effectively motivate employees and align with organizational goals and establish structured leadership development programs that identify and nurture high-potential employees so as to significantly influence performance of state-owned banks in Kenya.